Social Media, Halal Marketing and Consumer Behavior (Study in Fashion and Cosmetic Product) - Alam, Andi Rifqah Purnama; Hendriadi, Hendriadi; Suwardi, Wisda Zulaeha; Islamiyah, Nurhidayati; Monalisa, Monalisa (Universitas Muhammadiyah Makassar, 2023)
Consumers have become more sensitive to what they consume. Comprehensive information search and more accessible information acquisition will make it easier for consumers to make decisions. Social media is a supporting aspect for consumers in making decisions. Social media, which was previously used for personal communication, has now been used for communication in the broader business realm and plays a role as one of the supporters in the halal marketing process. The use of social media in marketing helps producers or sellers inform that the products being sold are halal products for Muslim consumers. Through social media, consumers can also easily obtain detailed information about a product before consumers make purchasing decisions. Halal marketing has become phenomenal in recent years because several products not in the form of food products have been branded as halal products. Products that are pioneers in halal branding include fashion and cosmetic products. This effort has altered the view that halal products are only limited to food products. This study used an interview method with 106 samples of productive age from several districts and cities in South Sulawesi Province. The results showed that 80% of the sample wanted cosmetic products to be halal to make purchasing decisions. In contrast, for fashion products, only 30% of the samples required the product to be halal to make a purchase decision.